Accelerated cognitive decline after the COVID‐19 pandemic in a community population of older persons with cognitive impairment: A 4‐year time series analysis in the Tokyo Metropolis area. Issue 3 (25th January 2023) - Matsui, Toshifumi; Mitsuma, Sayuri; Nagata, Akane; Matsushita, Sachio; Asahi, Toshiomi
Abstract : Aim: The coronavirus disease 2019 (COVID‐19) pandemic has led to lifestyle restrictions and might be associated with long‐term changes in cognitive function. The aim of the present study was to elucidate the overall effect of the COVID‐19 pandemic on the cognitive trajectory of a cohort of patients with cognitive impairment. Methods: We enrolled 160 patients who had been making regular visits to a medical center for dementia. Cognitive function was assessed based on changes in scores on the Mini‐Mental State Examination before and during the COVID‐19 pandemic throughout a 4‐year period. The trajectory of cognitive decline was determined by carrying out a time series analysis using a state‐space model. Results: Crude analysis showed that the Mini‐Mental State Examination scores decreased from 20.9 ± 4.4 points (mean ± SD) at the time of the initial cognitive assessments to 17.5 ± 5.6 points at the time of the final assessments, and the decline rate was 1.15 ± 1.78 points per year ( P < 0.0001). The time series analysis showed an accelerated cognitive trajectory after the COVID‐19 outbreak, and the average decline in the Mini‐Mental State Examination scores was 0.46 points (95% confidence interval 0.034–0.91) per year before the COVID‐19 pandemic, and a steeper decline of 1.87 points (95% confidence interval 1.34–2.67) per year after the outbreak. Conclusions: The COVID‐19 pandemic accelerated the rate of cognitive decline in patients with cognitive impairment fourfold in comparison with before the pandemic. Specific strategies designed for cognitively older people in the "new normal" will reconcile both requirements, reducing the risk of infection, and maintaining their physical and psychological well‐being. Geriatr Gerontol Int 2023; 23: 200–204 . Abstract : To address the adverse effects of the COVID‐19 pandemic on cognitive decline, we carried out a longitudinal study of ambulatory patients with cognitive impairment who had made regular clinic visits before and during the COVID‐19 pandemic throughout a 4‐year period. We used the data obtained from repeated assessments of their cognitive function to carry out a time‐series analysis using a state‐space model, and showed the accelerated the rate of cognitive decline in patients with cognitive impairment fourfold in comparison with before the pandemic.